Warga Jemaat Sebagai Kapita Selekta : Ujung Tombak Pembinaan Warga Gereja di Gereja HKBP Pansurnapitu - Julius Manahara Hutabarat; Netty Tesa Yolanika Sitompul; Pinondang Jetli Simanjuntak (Berkat : Jurnal Pendidikan Agama dan Katolik, 2025)
This research aims to explore the role of congregation members as capita selecta in developing church members at the HKBP Pansurnapitu Church. As the spearhead in the formation process, congregation members have a significant responsibility in implementing religious values ​​and strengthening community solidarity. Through a qualitative approach, this research analyzes how congregation members contribute to various aspects of church services, including organizing worship activities, faith education, and social participation. Data was collected through in-depth interviews with church leaders and congregation members, as well as direct observation of church activities. The research results show that the active involvement of congregation members not only strengthens the spiritual ties between them, but also increases the effectiveness of the formation programs implemented by the church. In addition, this research highlights the importance of support from church leaders in empowering congregation members to take a greater role in ministry. In this way, members of the congregation at HKBP Pansurnapitu function as vital agents of change in creating an inclusive and dynamic church environment. It is hoped that this research will provide insight into the development of more effective coaching strategies in the future.